Dragon ball the complete illustrations. Featuring the artwork from Dragon Ball and Dragon Ball Z - Toriyama, Akira 1955-2024 (The Art of Shonen Jump Edition, 2008)
Presents the illustrations from the manga "Dragonball," spanning 1984-1995, and an interview with artist Akira Toriyama